Somatic genomic variants in refractory cytopenia of childhood - Diego F. Coutinho; Mariana Boroni; Anna Beatriz W. Batalha; Danielle T. Vianna; Mayara Kalonji; Ana Paula S. Bueno; Soraia Rouxinol; Teresa S. Fernandez; Fabiana V. de Mello; Elaine S. Costa; Eliana Abdelhay; Bárbara C.R. Monte-Mór; et al. (Elsevier, 2021)
Despite all knowledge acquired regarding the mutational profile of pediatric myelodysplastic syndrome (MDS), the somatic genomic landscape underlying that disease remains unclear. We evaluated the presence of somatic variants in 37 genes related to myeloid malignancies through targeted NGS in 20 Brazilian patients with refractory cytopenia of childhood (RCC). Only 15% (3/20) of patients showed at least one somatic driver mutation - all in genes coding to regulators of cell signaling (TP53 and CBLB) or epigenetics (ASXL1 and DNMT3A). Interestingly, those variants were identified in patients with no detected clonal chromosomal abnormalities.